Spatial heterogeneity in hedonic house price models: the case of Austria - Helbich, Marco; Brunauer, Wolfgang; Vaz, Eric de Noronha; Nijkamp, Peter (Urban studies, 2014)
Modelling spatial heterogeneity (SH) is a controversial subject in real estate economics. Single-family-home prices in Austria are explored to investigate the c...